Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1074/jbc.m306056200
|View full text |Cite
|
Sign up to set email alerts
|

Id Proteins Negatively Regulate Basic Helix-Loop-Helix Transcription Factor Function by Disrupting Subnuclear Compartmentalization

Abstract: Id helix-loop-helix (HLH) proteins act as global regulators of metazoan cell fate, cell growth, and differentiation. They heterodimerize with and inhibit the DNA-binding function of members of the basic helixloop-helix (bHLH) family of transcription factors. Using real time fluorescence microscopy techniques in single living cells, we show here that nuclear pools of chromatin-associated bHLH transcription factor are freely exchangeable and in constant flux. The existence of a dynamic equilibrium between DNA-bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 49 publications
2
29
0
Order By: Relevance
“…Reduces Their Repression Activity in E-box-mediated Transcription-In agreement with the previous report (27), GFP-Id3 was distributed throughout the cells, and GFP-Id4 also exhibited diffuse nucleo-cytoplasmic localization (Fig. 7A).…”
Section: Increased Nuclear Export Of Id3 and Id4supporting
confidence: 79%
See 1 more Smart Citation
“…Reduces Their Repression Activity in E-box-mediated Transcription-In agreement with the previous report (27), GFP-Id3 was distributed throughout the cells, and GFP-Id4 also exhibited diffuse nucleo-cytoplasmic localization (Fig. 7A).…”
Section: Increased Nuclear Export Of Id3 and Id4supporting
confidence: 79%
“…Similar results were obtained in COS7, 293T, and U2OS cells (data not shown). Unlike GFP-Id2, fluorescently tagged Id3 was previously shown to be diffusely distributed throughout the cells (27). Thus, the cytoplasmic localization of GFP-Id2 is not cell type-dependent and is not a general effect caused by fusion with a fluorescence tag.…”
Section: The C-terminal Region Of Id2 Is Required For Cytoplasmicmentioning
confidence: 95%
“…Thus, the hypoxic cells adopt an immature phenotype where ID2 could play a significant part, primarily by sequestering E-proteins, preventing their ability to bind DNA in heterodimeric complexes together with bHLH proteins such as HASH-1 and dHAND (46,47). Recently, evidence have emerged demonstrating how ID proteins effectively sequesters pools of transiently diffusing E-proteins and abolish bHLH chromatin association (50). Furthermore, we have also demonstrated that hypoxia down-regulates gene expression of the dimerization partner for ID2, dHAND and HASH-1 (46), the Cotransfections were performed using 0.4 g/well of pFLAG-mHIF-1␣, expressing constitutively active HIF-1␣ or 0.4 g/well of empty pFLAG vector alone.…”
Section: Discussionmentioning
confidence: 99%
“…The Idb3 protein is known to play an important role in the control of cell differentiation by interfering with DNA binding of transcription factors. 23 Thus, the dramatic difference in transgene expression following activation of DC by CpG ODN plus CD40 antibody could have partly been due to downregulation of Idb3 in addition to upregulation and nuclear localization of transcription factors that facilitated efficient transgene expression.…”
Section: Discussionmentioning
confidence: 99%